Marketing Strategy Formulation with the Nine Core Elements of Marketing Framework: A Case Study of Bakpia Satu Hati MSME - Muhammad Faqih Asy-Syafi'iy; Berto Mulia Wibawa (Transpublika Publisher, 2026)
This research addresses the strategic challenges faced by Bakpia Satu Hati, a culinary MSME struggling to compete against established brands that utilize conventional marketing and monopolistic tourist channel practices. These barriers limit market expansion and digital technology adoption for new entrants. Consequently, this study aims to provide adaptive, innovative, and ethical strategic solutions for sustainable growth. To address this problem, the research formulates a marketing strategy using the Nine Core Elements of Marketing framework, which encompasses strategy (segmentation, targeting, positioning), tactics (differentiation, marketing mix, selling), and value (brand, service, process). The primary goal is to build a strategy focused not just on market share, but also on cultivating strong brand loyalty and positive brand perception. The analysis integrates several frameworks for a robust foundation. PESTEL examines macro-environmental changes, while Porter's Five Forces deepens competitor analysis. A TOWS matrix synthesizes internal and external factors, complemented by the 4C framework (Change, Competitor, Customer, Company) to provide a multidimensional view of the business landscape. The outcomes are expected to offer practical guidance for Bakpia Satu Hati's sustainable growth and contribute to the academic literature on innovative MSME marketing strategies in the culinary sector.